Epidemiology of Sports-Related Concussions in National Collegiate Athletic Association Athletes From 2009-2010 to 2013-2014: Symptom Prevalence, Symptom Resolution Time, and Return-to-Play Time. (January 2016) - Wasserman, Erin B.; Kerr, Zachary Y.; Zuckerman, Scott L.; Covassin, Tracey
Background: Limited data exist among collegiate student-athletes on the epidemiology of sports-related concussion (SRC) outcomes, such as symptoms, symptom resolution time, and return-to-play time. Purpose: This study used the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) to describe the epidemiology of SRC outcomes in 25 collegiate sports. Study Design: Descriptive epidemiology study. Methods: SRC data from the NCAA ISP during the 2009-2010 to 2013-2014 academic years were analyzed regarding symptoms, time to resolution of symptoms, and time to return to play. Findings were also stratified by sex in sex-comparable sports (ie, ice hockey, soccer, basketball, lacrosse, baseball/softball) and whether SRCs were reported as recurrent. Results: Of the 1670 concussions reported during the 2009-2010 to 2013-2014 academic years, an average (±SD) of 5.29 ± 2.94 concussion symptoms were reported, with the most common being headache (92.2%) and dizziness (68.9%). Most concussions had symptoms resolve within 1 week (60.1%); however, 6.2% had a symptom resolution time of over 4 weeks. Additionally, 8.9% of concussions required over 4 weeks before return to play. The proportion of SRCs that required at least 1 week before return to play increased from 42.7% in 2009-2010 to 70.2% in 2013-2014 (linear trend, P < .001). Within sex-comparable sports analyses, the average number of symptoms and symptom resolution time did not differ by sex. However, a larger proportion of concussions in male athletes included amnesia and disorientation; a larger proportion of concussions in female athletes included headache, excess drowsiness, and nausea/vomiting. A total of 151 SRCs (9.0%) were reported as recurrent. The average number of symptoms reported with recurrent SRCs (5.99 ± 3.43) was greater than that of nonrecurrent SRCs (5.22 ± 2.88; P = .01). A greater proportion of recurrent SRCs also resulted in a long symptom resolution time (14.6% vs 5.4%, respectively; P < .001) and long return-to-play time (21.2% vs 7.7%, respectively; P < .001) compared with nonrecurrent SRCs. Conclusion: Trends in return-to-play time may indicate changing concussion management practices in which team medical staff members withhold players from participation longer to ensure symptom resolution. Concussion symptoms may differ by sex and recurrence. Future research should continue to examine the trends and discrepancies in symptom resolution time and return-to-play time.